2017
DOI: 10.1016/j.biopsycho.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological investigation of emotional abnormalities in groups at risk for schizophrenia-spectrum personality disorders

Abstract: Both extreme levels of social anhedonia (SocAnh) and perceptual aberration/magical ideation (PerMag) are associated with risk for schizophrenia-spectrum disorders and with emotional abnormalities. Yet, the nature of any psychophysiological-measured affective abnormality, including the role of automatic/controlled processes, is unclear. We examined the late positive potential (LPP) during passive viewing (to assess automatic processing) and during cognitive reappraisal (to assess controlled processing) in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 95 publications
(119 reference statements)
7
21
0
Order By: Relevance
“…They suggested that 'modulation of neural responses by a cognitive emotion regulation strategy appears to be impaired in schizophrenia during the first two seconds after exposure to unpleasant stimuli. ' Moreover, it was reported that people at risk for schizophrenia spectrum disorder such as social anhedonia also have abnormalities in emotion regulation processing, which is reflected by enhanced LPP amplitude when passively viewing negative pictures compared to controls 67 . The absence of any post-priming LPP modulation from either ER-related and ER-unrelated conditions across schizotypy and control groups, leads us to speculate that deficits displayed by individuals with schizotypal traits in the late stage of explicit emotion regulation are not mirrored by deficits at the same stage of the implicit regulation.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that 'modulation of neural responses by a cognitive emotion regulation strategy appears to be impaired in schizophrenia during the first two seconds after exposure to unpleasant stimuli. ' Moreover, it was reported that people at risk for schizophrenia spectrum disorder such as social anhedonia also have abnormalities in emotion regulation processing, which is reflected by enhanced LPP amplitude when passively viewing negative pictures compared to controls 67 . The absence of any post-priming LPP modulation from either ER-related and ER-unrelated conditions across schizotypy and control groups, leads us to speculate that deficits displayed by individuals with schizotypal traits in the late stage of explicit emotion regulation are not mirrored by deficits at the same stage of the implicit regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has shown that positive and negative schizotypy are associated with both shared and unique emotional abnormalities (Fung et al, 2017;Martin et al, 2017). For instance, higher levels of positive schizotypy traits and higher levels of negative schizotypy traits are associated with higher trait negative affect.…”
Section: Introductionmentioning
confidence: 99%
“…Although people with SocAnh engage in fewer social interactions, they report doing so by choice (Brown et al, 2007;Kwapil et al, 2009). Thus, people with elevated levels of SocAnh exhibit a genuine preference for solitude, which has been differentiated from introversion (Martin, Karcher, Bartholow, Siegle & Kerns, 2017) and social anxiety (Brown et al, 2007;Brown, Silvia, Myin-Germeys, Lewandowski, & Kwapil, 2008;Cicero, Krieg, Becker, & Kerns, 2016). This lack of pleasure and withdraw from social connection contrasts the well-documented "need to belong" (Brown et al, 2007;Silvia & Kwapil, 2011), which describes the motivation to pursue and enjoy the connection with others as stemming from a fundamental human need.…”
Section: Introductionmentioning
confidence: 99%